1992
DOI: 10.1111/j.1399-3011.1992.tb01553.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic hexapeptides derived from the human thymopoietin III

Abstract: Six diastereoisomeric cyclic hexapeptides of the partial sequence 39‐44 of human thymopoietin III in which each residue was replaced with the d‐amino acid were synthesized. In contrast to expectations, the yields from cyclization were not influenced by the location of the d‐residue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 8 publications
2
8
0
1
Order By: Relevance
“…Interestingly, the use of D-amino acids in promoting cyclization of 12-membered peptides has been studied. 28 The present observation validates such a use and indicates that D-serine could be used as a design element that could force the stevastelins to adopt a specific dominant conformation in solution. Further synthetic manipulations could provide insight on this hypothesis.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, the use of D-amino acids in promoting cyclization of 12-membered peptides has been studied. 28 The present observation validates such a use and indicates that D-serine could be used as a design element that could force the stevastelins to adopt a specific dominant conformation in solution. Further synthetic manipulations could provide insight on this hypothesis.…”
Section: Discussionsupporting
confidence: 83%
“…Indeed this strategy has been employed to improve the yields of various peptide cyclizations 32,33 . For two diastereomeric short peptide sequences that differ only in α-carbon configuration at the terminal residues, cyclization is favoured for the diastereomer that contains both a d-and an l-residue at its termini 34 .…”
Section: Conformational Elements That Help Bring the Ends Togethermentioning
confidence: 99%
“…NMR studies have shown that including a D -amino acid in short cyclic pentapeptides or hexapeptides can stabilize a characteristic backbone conformation by inducing a bII’ turn motif with the D -amino acid in the i+1 position [10, 12, 14]. Thus, this class of cyclic peptides is thought to provide a defined backbone scaffold for presenting different short peptide binding motifs.…”
Section: Discussionmentioning
confidence: 99%
“…A number of such small cyclic peptides ligands have been developed to bind to diverse target proteins. These include RGD (Arg-Gly-Asp)-containing integrin ligands [11, 12, 15], analogues of the Leu-Asp-Thr sequence of mucosal addressin cell adhesion molecule-1 (alpha(4)beta(7) integrin antagonists) [3], somatostatin receptor agonists [26], human thymopoietin III analogs [14], and CXCR4-chemokine antagonists [9]. Motivated by these previous successes for this class of cyclic peptides, we have synthesized and tested cyclic hexapeptides with a single D -amino acid that contain the secretin receptor endogenous agonist WD motif.…”
Section: Discussionmentioning
confidence: 99%